TECHNOLOGIA KSZTAŁCENIA I PEDAGOGIKA MEDIALNA JAKO NAUKI O MEDIACH - Strykowski, Wacław (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
The aim of the article is to show the origin, the subject matter and the development of two disciplines connected with media: technology of education and medial pedagogy. The former is shown in three stages - regarding the extension of field interest. Nowadays educational technology is not only a science of media, but also a science of designing, performing and assessing educational processes and systems. On the other hand, all aspects of media (both school media and mass-media) are within the interest of medial pedagogy, social demand for which is presented in the article.
Keywords: Technologia kształcenia; Technology of education; Pedagogika medialna; Media pedagogy; Środki dydaktyczne; Didactics media; Media; Neodidagmata; Dyscyplina pedagogiczna; Pedagogy branch